Analysis of stress distribution on the bone around an implant placed in the anterior maxilla using three different abutment angulations by means of finite element analysis - Snehal Shende; Amit Jadhav; Dhairaysheel N Edake; Amit Hemraj Patil; Hansraj Patil; Nitu Agrawal (Journal of Pharmacy and Bioallied Sciences, 2021)
Aim: the aim of the study was to study the effect of stress distribution on the bone around an implant using angled abutments by means of finite element analysis in the anterior maxillary region. Materials and Methods: A three-dimensional (3D) model of the of patient's maxilla of right central incisor: tooth, bone, crown, implant, and abutment system were used in this study. The models were designed for three situations with straight abutment, i.e. 0°, 15°, and 20° angled abutment. The load of 178N was applied on the cingulum area of the prosthesis at an angle of 130° in relationship with the long axis of the implant. After applying the static loads on each model, the stress generated in the bone and the implant was recorded. The results will be analyzed by analysis of variance test. Results: The cortical and cancellous on Mises stresses in 20° abutment model were found to be maximum as compared to 15° abutment followed by 0° abutment. The stress was concentrated in the implant-abutment joint area. The overall stresses in 20° abutment model were found to more than 15° abutment followed by 0° abutment. The magnitude of stresses increased as the angulations increased. Conclusion: From the conclusions of this study, the stress is more multiplied in angled abutments, hence care needs to be taken when restoring implants using angled abutments, especially in patients with heavy masticatory load or when planning for cantilevering of restorations in these angled implant restoration.